A strategy for the sustainability of Peru’s blueberry exports:diversification and competitivenes - Guzmán Valle, María de los Ángeles (2024)
The study examines how Peru could maintain the sustainability of its blueberry exports through market diversification and competitiveness. Using a quantitative approach, the Herfindahl– Hirschman Index (HHI) and the Balassa Index were calculated. The results showed impressive growth in key markets such as the United States, where exports grew by an average of 115.03% annually, and robust growth in the Netherlands and the United Kingdom. Despite these increases, the study identified a high concentration in specific markets, particularly in the United States, where the HHI ranged from 2896 to 3828 throughout the evaluated period, indicating significant dependence. Regarding the RCA, the values showed that Peru has maintained a solid comparative advantage, especially towards the United States, where the values fluctuated between 0.09 and 0.55 throughout the study, indicating specialization and efficiency in the export of blueberries to this market. The conclusions highlight that, although Peru has achieved remarkable growth in its blueberry exports and has demonstrated competitive capabilities, it faces the challenge of effectively diversifying its export markets. Recommendations include expanding the exploration of new markets and improving logistic infrastructure and agricultural practices to foster environmental sustainability, as well as adapting marketing strategies to meet the demands of emerging markets and international regulations.